Influência da expansão rápida da maxila no volume do seio frontal - Furtado, Gisela Crippa (2016)
There are several studies about the Rapid Maxillary Expansion (RME) in the literature, however, the investigations don’t assess his relationship with possible volumetric changes of the frontal sinus, compromising forensic identification procedures. The objective of this observational analytical study was to verify the hypothesis that the frontal sinus remains unchanged with RME. We selected 16 patients (10 women and 6 men) between 10 and 15 years old with maxillary deficiency and frontal sinus intact. Patients were treated with RME via the Hyrax device. It performed Cone Beam Computed Tomography (CBCT) before RME (T1) and 120 days after the retention period (T2), to analyze dimensional changes in the frontal sinus. The frontal sinus area was surrounded with a table digitizer G-Pen F350 (Genius, Taipei, Taiwan), and the images were measured in various cuts for subsequent calculation of volume (mm3). To compare the difference between average volume obtained before and after RME was used paired t test and was discounted increasing normal volume expected for the age of the study patients during the 4-month study period. The average volume of the frontal sinus before the ERM was 4.38 mm3 (± 2.77) and after RME was 4.29 mm3 (± 2.54) taking into account the value of the normal frontal sinus growth, not statistically significant difference was encountered. The hypothesis that the frontal sinus does not undergo volumetric changes with rapid maxillary expansion was accepted